Students’ E-Learning Management at Home During Covid-19 Pandemic - Indah Komsiyah (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to obtain e-learning management carried out by students at home during the covid-19 pandemic. This research is qualitative with a survey method. This study offered an in-depth analysis of student management in managing online learning during a pandemic. The learning management process applied by teachers and students has different ways. The participants were 100 students. The data collection process used observation, documents and interviews. The data analysis technique used is l) data reduction, 2) data display; and 3) concluding/verification. The results showed that student learning management during e-learning was not good because they experienced a decrease in the discipline. Some of these findings were delays in submitting assignments, being passive, not opening zoom videos, not utilizing online learning resources, and not preparing and reading materials. However, students still showed motivation to do group assignments and attend online classes. Overall, students are more comfortable studying offline than online. The results of this study have implications for the understanding of teachers to provide motivation during online classes and stimulate students so that online learning activities are like offline